PEMBERDAYAAN USAHA SHUTTLECOCK DI DESA GADINGAN KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Cahyadin, Malik; Ayuninggar, Lintang (Universitas Negeri Yogyakarta, 2016)
This activity aims to facilitate the development of SME's Shuttlecock inSukoharjo. It was become a business cluster for supporting local economic development. The SME that becomes the partners in this activity were Aiwan Shuttlecock and Delima Shuttlecock. There are three activities which have been done for them, namely: production management, marketing, and accounting. The results of this activity involve: (1) SME entrepreneurs understood the good production process of shuttlecock based on the work operational standards; (2) SME entrepreneurs were able to use marketing medias to promote shuttlecock product in the form online medias; and (3) SME used accounting for financial bookeeping and accessing financial resource both government fund and private fund. In the future, the government of Sukoharjo District can promote SME's Shuttlecock as local economic icon